2010
DOI: 10.1007/s00256-010-0911-7
|View full text |Cite
|
Sign up to set email alerts
|

Finger fractures imaging: accuracy of cone-beam computed tomography and multislice computed tomography

Abstract: Cone beam CT may be considered a valuable imaging tool in the preoperative assessment of finger fractures, when MSCT is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 25 publications
2
40
1
2
Order By: Relevance
“…Also pointing in this direction is the good inter-rater reliability of the RED-CBCT in this particular task. Our assumption would also be consistent with the literature, that has found no difference between CBCT and MDCT in the assessment of the fragment number [13,29]. …”
Section: Discussionsupporting
confidence: 91%
“…Also pointing in this direction is the good inter-rater reliability of the RED-CBCT in this particular task. Our assumption would also be consistent with the literature, that has found no difference between CBCT and MDCT in the assessment of the fragment number [13,29]. …”
Section: Discussionsupporting
confidence: 91%
“…The impact of the imaging modality on patient management could not be investigated due to differing patient populations in the two groups. In a previous comparison of CBCT and MSCT imaging for interphalangeal fractures, the CBCT scanner was found to have 100 % sensitivity and specificity for the detection of articular involvement and there was no significant difference between modalities in the number of bone fragments detected [57]. Technical studies from various applications have shown CBCT scanners to be comparable to MSCT in geometric accuracy, making them well-suited for pre-operative planning [20,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…the number, size and location of bone fragments. 2 We have found the use of CBCT to be extremely helpful in evaluating fractures involving the PIPJ. CBCT's are quick to perform, add greater detail than conventional X-rays and help guide appropriate management (Figures 1 and 2).…”
Section: Cone Beammentioning
confidence: 99%